Abordagem multivariada de características fisiológicas foliares de cana-de-açúcar sob estresse - Santos, Hugo Rafael Bentzen (2015)
The sugarcane is one of the most important agricultural commodities in the world, being the main raw material for sugar production and bioenergy. The expansion of cultivated area and increased productivity for this crop have been limited by low water availability present in some areas. Drought events of the past four years strongly have affected the productivity of sugarcane deployed in southeastern Brazil, has induced the demand for more cultivars tolerant to seasonal droughts contributing to reduction of negative impacts on crop production. Thus, the aim of this work was to analyze short-term adjustment capacity of foliar physiological responses that would allow the homeostasis of three most cultivated varieties of sugar-cane in Minas Gerais subjected to different water stress levels imposed by polyethylene glycol-PEG 6000. The experiment was conducted in a greenhouse, RB 867515, SP 80-1816 and SP 81-3250 cultivars were submitted to different levels of water stress induced by PEG (first cycle 0, -0.1, -0.3 and - 0,6MPa / third cycle 0, -0.2, -0.6 and -1.2MPa) and rehydration. The variables analyzed were leaf physiological and behavioral aspects of cultivars, through its gas exchange, leaf water potential, antioxidant enzyme activities, hydrogen peroxide content and amount of malondialdehyde and all data was submitted to principal component analysis. The cultivar RB 867 515 showed the largest decreases in gas exchange, compared to other cultivars, decreased by 90 and 97% for photosynthesis and stomatal conductance, respectively. The leaf water potential reachead up to -1.98MPa in the cultivar SP 81-3250 during stress -1.2MPa. Lipid peroxidation was even higher than 192% in the treatment -1.2MPa the cultivar SP 81-3250. The increase of proline for the most stressed treatments was pronounced for SP 80-1816 and RB 867515 cultivars, while in intermediate stress the accumulation of carbohydrates and protein was more pronounced in the SP 82-3150. During rehydration all physiological variables returned to normal levels equal to the control showing a quick resilience of plants. SP 80-1816 and SP 81-3250 cultivars showed the highest and lowest plasticit to high levels of water stress during short term, respectively. RB 867515 along with the SP 80-1816 increased proline levels in order to reduce the antioxidant enzymes in the most severe treatment, while SP 81-3250 had an increase in carbohydrate and protein content in an attempt to maintain its turgor when placed in intermediary treatments.